Morphometric analysis of pebbles in verification of transport processes and interpretation of palaeoenvironment: A case study from the Ogwashi Formation (Oligocene), Niger Delta Basin, Nigeria - Ogbe, Ovie B.; Osokpor, Jerry; Emelue, Chukwunomso V.; Ocheli, Azuka (Geologos, 2023)
The present paper discusses a palaeoenvironmental interpretation of the Oligocene Ogwashi Formation (Niger Delta Basin, Nigeria) through morphometric analysis of pebbles, a research method essentially depending on the quantitative evaluation of pebble size and shape which change during transport processes in a range of depositional environments. The relationship of bivariate and ternary-diagram plots of independent functions was determined from freshly exposed sandstone sections in quarries at Ibusa, near Asaba, Nigeria. The grain size of pebbles ranges from fine (11.00 mm) to very coarse (41.33 mm), with a mean size of 21.05 mm (coarse pebbles). A bivariate plot of the flatness index vs maximum projection sphericity index shows 37% of the pebbles to fall within a beach (marine) environment, and 33% within a fluvial environment; the remaining 30% are uncertain. The maximum projection sphericity index vs oblate-prolate index bivariate plot indicates that 47% of pebbles fall within a marine environment and 22% within a fluvial environment, while the remaining 31% are uncertain. The sphericity-form ternary diagram plot shows that the pebbles primarily comprise bladed, platy, very bladed and very platy of near-equal proportions with minor elongate and very elongate stones, which suggests that the pebbles are diverse in origin. The sphericity-form bivariate plot indicates that the pebbles are largely of disc and blade shapes with a minor number of spherical and rod shapes. The near-equal proportion of pebbles in different segments of the bivariate and ternary diagram plots, and the wide distribution of the pebble grain sizes and shapes suggest the Ogwashi Formation is composed of redeposited sediments that likely were transported and deposited in a mix of marine and fluvial settings with possible transitional environments. In other words, the pebbles can be interpreted as marine-influenced fluvial sediments in marginal-marine settings.